835 F.I.T for Discharge? Role of Faecal Immunochemical Testing (FIT) in Ruling Out Primary Bowel Cancer: A Review of Current Outcomes. (19th August 2022) - Krishna, Arun; Ferrara, Giovanni; Edwards, Joshua; Lala, Anil
Abstract: Aim: NICE recommends a FIT <10 may not warrant an Urgent Suspected Cancer(USC) Referral. We aim to assess current outcomes at a local level. Secondary aims included whether a high FIT(>100) determines increased cancer risk and whether a moderate FIT(10–100) warrants a USC referral. Method: We retrospectively looked at patients who received a FIT between June-December 2020 in North-West Wales. These were divided into 3 groups: negative FIT(<10), moderate FIT(10–100) and high FIT(>100). They were followed-up for a year to determine the result of further investigations such as Endoscopies, CT Colons or CTs. The histology results from polyps/biopsies/specimens from Endoscopy/Surgery were recorded. Results: A total of 909 patients received a FIT, 180 excluded due to no result. 557 were negative, 125 moderate and 47 high. 2 of 557(0.36%) in the negative FIT group had cancer, however histology of both showed Squamous Cell Carcinoma from Anal Cancer. 4 of 125(3.2%) in the moderate FIT group and 10 of 47(21.27%) in the high FIT group had cancer. Polyp histology demonstrated high-grade dysplasia in 1(2.13%) in the high, 3(2.4%) in the moderate and 0 in the negative Group. Conclusions: Inappropriate investigations and delayed diagnosis can both have drastic clinical and financial implications. Our results show that a negative FIT, with a thorough history and examination, should prevent a need for a USC referral for primary bowel cancer. Patients with high FIT could proceed to investigation, while moderate FIT may need further assessment.